Frequency of the IVS-10nt546 mutation in 44 Turkish phenylketonuria patients - Özgüç, Meral; Özalp, İmran and Coşkun, Turgay and Yılmaz, Engin and Erdem, Hayat and Ayter, Şükrüye (The Turkish Journal of Pediatrics, 1993)
The newly identified point mutation in intron 10 of the phenylalanine hydroxylase gene activates a cryptic splice site and results in an in-frame insertion of nine nucleotides between exons 10 and 11 of the processed transcript. This mutation is observed in association with haplotype 6 of phenylketonuria chromosomes. Since in Turkey, haplotype 6 is observed in 40 percent of mutant phenylketonuria alleles, the aim of this study was to establish the incidence of this particular mutation. Forty-four classical phenylketonuria patients were studied and the frequency of the intron 10 splicing mutation was determined to be 31 percent.